Esophageal Foreign Bodies - Hussen, Waleed M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The removal of an impacted foreign body in the esophagus is still a common practice in the Thoracic Department of the Medical City Hospital .The objective of this study is to cast a light on this rather a common phenomenon in our country , its risks and its management. Patients and Methods: This is a retrospective study of 120 patients with foreign bodies in the esophagus managed successfully in our department during five years period 1998 – 2002 inclusive .The study included 65 males and 55 females . Their ages range between I year and 75 years. The most common age group was less than 10 years , which constitutes about 30% of our patients .Varieties of foreign bodies were encountered ,their ways of presentation , clinical findings and radiological appearances will be prescribe . Results: Successful removal of the foreign bodies was done in most of the cases .In 4patients esophageal dilatation was done for an area of stricture on which the foreign body was impacted. Surgery was necessary in two patients for the removal of foreign bodies which were impossible to be removed endoscopically . Conclusion: Rigid esophagoscopy under general anesthesia is the procedure of choice for foreign body removal and nearly all the cases could be considered preventable.